Correlates of social media fatigue and academic performance decrement: A large cross-sectional study - Malik, Aqdas; Dhir, Amandeep; Kaur, Puneet; Johri, Aditya (Information technology & people (West Linn, Or.), 2021)
PurposeThe current study aims to investigate if different measures related to online psychosocial well-being and online behavior correlate with social media fatigue.Design/methodology/approachTo understand the antecedents and consequences of social media fatigue, the stressor-strain-outcome (SSO) framework is applied. The study consists of two cross-sectional surveys that were organized with young-adult students. Study A was conducted with 1,398 WhatsApp users (aged 19 to 27 years), while Study B was organized with 472 WhatsApp users (aged 18 to 23 years).FindingsIntensity of social media use was the strongest predictor of social media fatigue. Online social comparison and self-disclosure were also significant predictors of social media fatigue. The findings also suggest that social media fatigue further contributes to a decrease in academic performance.Originality/valueThis study builds upon the limited yet growing body of literature on a theme highly relevant for scholars, practitioners as well as social media users. The current study focuses on examining different causes of social media fatigue induced through the use of a highly popular mobile instant messaging app, WhatsApp. The SSO framework is applied to explore and establish empirical links between stressors and social media fatigue.